The Paladin Prophecy - Frost, Mark, 1953- (Random House, 2012)
A fifteen-year-old boy who has spent his entire life trying to avoid attention finds himself in the middle of a millenia-old struggle between titanic forces when he is simultaneously recruited by an exclusive prep school and followed by sinister agents.